Project ATLAS: An Integrated Learning and Development Management System with Automated CPD/PD Credit Tracking and Competency-Based Talent Mapping Using ISO/IEC 25010:2023 Quality Metrics (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Traditional educational training frameworks in public sector governance often rely on disconnected learning platforms, slow manual workflows for tracking professional development (CPD/PD) credits, and fragmented visibility between training initiatives and workforce skill profiles. To address these bottlenecks, this study designed, developed, and validated Project ATLAS (Advanced Training and Learning Administration System), an integrated Learning and Development Management System featuring automated CPD/PD credit tracking, role-stratified administrative dashboards, and competency-based talent mapping engines. Built on a custom Model-View-Controller (MVC) architecture in PHP, a lightweight server-side hypermedia stack, MySQL relational database, and secured through Cloudflare Zero Trust outbound tunnels, the system replaces error-prone manual processes with reliable automation. The platform's architectural quality and functional suitability were evaluated using a descriptive engineering design aligned with the ISO/IEC 25010:2023 software product quality model. A purposive sample of 15 technical experts and administrative evaluators assessed the system, yielding an overall quality score of 3.91 out of 4.00 (SD = 0.11). Security (M = 3.96, SD = 0.05) and Safety (M = 3.94, SD = 0.08) dimensions received the highest ratings. These findings demonstrate that custom MVC backend layers combined with optimized relational database constraints deliver enterprise-grade security, minimized network latencies, and high administrative efficiency in resource-constrained public educational settings. Project ATLAS offers a scalable, compliant, data-driven architecture that mitigates administrative backlogs, preserves institutional memory, and aligns workforce capabilities with institutional needs.